EKOLOGI DAN PERSEBARAN GEWANG (Corypha utan Lamk.) DI SAVANA TIMOR, NUSA TENGGARA TIMUR - Tukirin Partomihardjo; BP Naiola (Research Center for Biology-Indonesian Institute of Sciences, 2009)
A study of the distribution and ecology of Corypha utan Lamk. (gewang) within the natural habitat of savana ecosystem at Usapisonba'i village area, Kecamatan Nekamese, Kabupaten/Regency Kupang, East Lesser Sunda Islands was conducted to gain an understanding factors controlling distribution and dynamics populations of the species. Three plots with total of 2.1 ha were established at different sites. Reconnaissence throughout the study area revealed that gewang grows in the lowlands below 200 m altitude, but away from the immmediate vicinity of the sea. Populations were studied within different savana types. It was concluded that gewang appears to be relatively associated to the open areas. The abundance of gewang within the study area formed the main savana vegetation as savanna gewang type. Distribution pattern of gewang within the study area tend to be concentrated at the lower part of the plots in particular at relatively flat areas. Examination of seedling and sapling densities in relation to parent trees revealed a large number of propagules fallings to disperse, and in consequence tendencies toward dumb distributions. The seedlings tend to grow under dead parent tree and or at flat of lower areas. Based on the population structure, gewang revealed has good regeneration strategy with high population of younger stages.